Déficit de vitamina D. Revisión epidemiológica actual - Barberán M., Marcela; Aguilera C., Germán; Brunet L., Luis; Maldonado C., Felipe (Revista Hospital Clínico Universidad de Chile, 2014)
Vitamin D is a liposoluble hormone that exists in two molecular forms. Ergocalciferol (vitamin D-2) and colecalciferol (vitamin D-3). Vitamin D-3 is produced in the skin by the action of UV-B radiation. Both forms are metabolized by the liver to 25-hydroxy-Vit D (25OHD) and later in the kidney to the active form 1,25-dihydroxy-Vit D. This form promotes bone mineralization by intestinal absorption of calcium and phosphate. Normal levels of 25OHD are associated with less fracture, normal neuromuscular and immune function and possibly have a preventive effect on certain types of cancer. The Endocrine Society’s Clinical Practice Guidelines recommends that optimal plasma levels of 25OHD are above 30 ng/ml, insufficiency between 21 and 29 ng/ml and deficiency below 20 ng/ml. The prevalence rate of 25OHD deficit is about 2 to 90% in different populations. Risk factors of Vitamin D deficit like year season, skin pigmentation, sunlight exposition, use of sunblock and inadecuate Vitamin D ingestion, together with different measurement echniques explain the variability of results between epidemiological studies. An important risk group is the health professionals that re not exposed to sunlight. There are no studies that describe the prevalence in this population in Chile.